2019
DOI: 10.1155/2019/3590584
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Landscape of Gut System of Guppy Fish (Poecilia reticulata) Plays an Outstanding Role in Adaptation Mechanisms

Abstract: Microbial consortium that is present in fish gut systems works together to achieve unknown specific roles. Here, we collected guppy fish from hydrocarbon- and trace metal-contaminated wastewater to assess the relationships between gut microbiota and host fish adaptation. Targeted genes and 16S rRNA amplicon sequencing have been used to identify gut bacteria of guppies. Mineral-conditioned medium contributes to identify bacteria with the ability to grow and/or to tolerate hydrocarbon and trace metals. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
15
0
3
Order By: Relevance
“…The emulsification index is a direct method for demonstrating the ability of strains to produce biosurfactants or not [13]. Those molecules have been known to form emulsions between two immiscible liquids [34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emulsification index is a direct method for demonstrating the ability of strains to produce biosurfactants or not [13]. Those molecules have been known to form emulsions between two immiscible liquids [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…An overnight of 5mL of bacterial culture have been done. The emulsification index (EI24) was calculated as an indicator for BLM as previously demonstrated [13]. The medium was adjusted to pH 7.2 and supplemented with gasoline or diesel fuel (1 mL for 300 mL of medium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 5 mL of bacterial overnight culture, the emulsification index (EI24) was calculated as an indicator for BLM production as previously demonstrated [ 5 ]. The medium was adjusted to pH 7.2 and supplemented with gasoline or diesel fuel (1 mL for 300 mL of medium).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study in our laboratory showed that Shigella sp. isolated from Brazzaville wastewater were able to emulsify hydrocarbon from gasoline and/or diesel fuel [5]. According to amphipathic features, biosurfactants display a variety of surface activities, which explain their application in several fields related with emulsification, foaming, detergency, wetting, dispersion, pathogenicity, and solubilisation of hydrophobic compounds [6,7].…”
Section: Introductionmentioning
confidence: 99%